Bezpieczeństwo w systemach logistycznych przedsiębiorstw funkcjonujących w województwach zachodniej Polski = Security in the logistics systems of enterprises operating in the voivodeships of western Poland - Siuda, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the current state of security of logistics systems in selected enterprises based in the western part of Poland, i.e. in the West Pomeranian, Lubusz and Lower Silesian Voivodeships. The article consists of two main parts.
Keywords: bezpieczeństwo; logistyka; zagrożenia; system logistyczny; analiza ryzyka; security; logistics; threats; logistics system; risk analysis